Nanoparticle / high-molecular polymer composite scaffold with good dispersibility and antioxidant activity as well as preparation method and application of nanoparticle / high-molecular polymer composite scaffold

By combining oleic acid-coated manganese-replaced white phosphorus calcium stone nanoparticles with polycaprolactone, a composite scaffold with good dispersion and antioxidant activity was prepared, which solved the problems of donor area complications, immune rejection risks and oxidative stress in traditional bone defect treatment methods, and achieved bone defect repair and regeneration in the oxidative stress environment.

CN119841289AActive Publication Date: 2025-04-18JILIN UNIVERSITY
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510336796.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-21
Publication Date
2025-04-18
Estimated Expiration
2045-03-21

AI Technical Summary

Technical Problem

Traditional bone defect treatment methods have problems such as donor area complications, risk of immune rejection and scarcity of donor sources. Bone defects are often accompanied by oxidative stress, resulting in osteoblast apoptosis and bone aplasia.

Method used

Nanoparticles of oleic acid-coated manganese-substituted white phosphorus calcium stone were combined with polycaprolactone to prepare nanoparticle/polymer composite scaffolds with good dispersion and antioxidant activity through 3D printing.

Benefits of technology

This composite scaffold exhibits antioxidant activity in an oxidative stress environment, promotes bone biological effects, and achieves the improvement of mechanical properties and optimization of cell interactions through uniformly dispersed nanoparticles, solving the problems of nanoparticle aggregation, mechanical properties decline and oxidative stress status that cannot be alleviated.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841289A_ABST
    Figure CN119841289A_ABST
Patent Text Reader

Abstract

The invention is suitable for the technical field of biology, and provides a nanoparticle / high-molecular polymer composite scaffold with good dispersibility and antioxidant activity, and a preparation method and application thereof. The method comprises the following steps: adding an aqueous solution of calcium chloride, magnesium chloride, manganese chloride and sodium phosphate into a mixed solution of oleic acid and absolute ethyl alcohol, forming oleic acid-coated manganese-substituted pandermite nanoparticles by virtue of a hydrothermal method, and forming the composite scaffold by virtue of high interfacial compatibility of oleic acid and a high-molecular polymer. According to the invention, manganese coated with oleic acid is used for replacing white calcomanite nanoparticles to exert anti-oxidation and osteogenic biological effects in an oxidative stress bone defect microenvironment, and uniform dispersion of the nanoparticles in a high-molecular polymer is realized through the constructed nanoparticle / high-molecular polymer composite scaffold. The two strategies cooperatively regulate and control repair of the oxidative stress bone defect area, and the problems that nanoparticles aggregate, the mechanical performance is reduced, the cell interaction is limited, and the oxidative stress state cannot be relieved are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biotechnology, and in particular relates to a nanoparticle / high molecular polymer composite scaffold with good dispersibility and antioxidant activity, and a preparation method and application thereof. Background Art

[0002] Bone defects are one of the major challenges facing the global health field. Although traditional treatments such as autologous bone transplantation and allogeneic bone transplantation have certain effects, they face problems such as donor site complications, risk of immune rejection, and scarcity of donor sources. In addition, bone defects are often accompanied by local microvascular rupture and insufficient oxygen supply, forming a hypoxic microenvironment, leading to increased levels of reactive oxygen and reactive nitrogen, and inducing oxidative stress. Excessive reactive oxygen not only induces apoptosis of osteoprogenitor cells and mature osteoblasts, but also inhibits the expression of key osteogenic markers, thereby disrupting the osteogenic differentiation process and ultimately hindering bone regeneration. In view of these challenges, there is an urgent need to develop new treatment strategies to effectively address bone defects and achieve their repair and regeneration.

[0003] Tissue engineering technology provides a new idea for the development of scaffold materials with both mechanical support and osteoinduction functions. Among them, polycaprolactone (PCL) has become a matrix material widely used in 3D printing due to its excellent biocompatibility, mechanical properties and easy processing. However, polycaprolactone itself has the problems of insufficient mechanical strength and lack of biological activity, making it difficult to effectively induce osteogenic differentiation. Traditional methods introduce functional inorganic nanoparticles into polymer matrices to provide bioactive ions, but due to the poor interfacial compatibility between functional inorganic nanoparticles and polymer matrices, it often leads to problems such as nanoparticle aggregation, decreased mechanical properties and limited cell interactions. For this reason, the present invention proposes a nanoparticle / polymer composite scaffold with good dispersibility and antioxidant activity, as well as a preparation method and application thereof. Summary of the invention

[0004] The purpose of the present invention is to provide a nanoparticle / polymer composite scaffold with good dispersibility and antioxidant activity, and a preparation method and application thereof, in order to solve the problems raised in the above background technology.

[0005] The purpose of the present invention is achieved through the following technical solutions: An oleic acid-coated manganese-substituted whitlockite nanoparticle is prepared by the following method: A mixed aqueous solution of calcium chloride, magnesium chloride, manganese chloride and sodium phosphate is added to a container containing oleic acid and anhydrous ethanol, and after being stirred evenly, the reaction mixture is reacted at 150-200° C. for 10-12 h to obtain a mixture of manganese-substituted leucodelite nanoparticles immersed in a mixed solution of oleic acid and ethanol, and after centrifugal washing, oleic acid-coated manganese-substituted leucodelite nanoparticles are obtained; The molar ratio of calcium chloride, magnesium chloride, manganese chloride and sodium phosphate is 9:0-1:0-1:6; and the volume ratio of oleic acid and anhydrous ethanol is 4-5:16.

[0006] Furthermore, the molar ratio of the total molar amount of calcium chloride, magnesium chloride and manganese chloride to sodium phosphate is 9:1:6.

[0007] An application of the oleic acid-coated manganese-substituted whitlockite nanoparticles described above is used in preparing a nanoparticle / high molecular polymer composite scaffold with good dispersibility and antioxidant activity.

[0008] An application of the oleic acid-coated manganese-substituted whitlockite nanoparticles described above is used in the preparation of drugs for anti-oxidation and bone defect repair.

[0009] A nanoparticle / polymer composite scaffold with good dispersibility and antioxidant activity is prepared by the following method: Take the oleic acid-coated manganese-substituted white calcium phosphate nanoparticles described above, add them to polycaprolactone dissolved in dichloromethane, continue stirring until the dichloromethane evaporates, and use the fused deposition modeling technology to prepare a composite scaffold with uniform pore size and specific shape using a 3D printer to obtain a nanoparticle / polymer composite scaffold with good dispersibility and antioxidant activity.

[0010] Furthermore, the mass ratio of the oleic acid-coated manganese-substituted whitlockite nanoparticles to polycaprolactone is 1:1-10.

[0011] Furthermore, the mass fraction of the oleic acid-coated manganese-substituted whitlockite nanoparticles is 30%.

[0012] An application of the nanoparticle / high molecular polymer composite scaffold with good dispersibility and antioxidant activity as described above is used in preparing a composite scaffold for promoting bone defect repair under oxidative stress.

[0013] Compared with the prior art, the present invention has the following beneficial effects: The present invention proposes a method with a simple synthesis process and low cost, which has two significant advantages and technical contributions. On the one hand, oleic acid-coated manganese-substituted whitlockite nanoparticles are used to exert antioxidant and osteogenic biological effects in the oxidative stress bone defect microenvironment. On the other hand, the nanoparticles are uniformly dispersed in the polymer by constructing a nanoparticle / polymer composite scaffold. These two strategies synergistically regulate the repair of oxidative stress bone defect areas, solving the problems of nanoparticle aggregation, decreased mechanical properties, limited cell interactions, and the inability to alleviate oxidative stress. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 The figure shows the particle size distribution diagram, TEM diagram, XRD diagram and EDS energy spectrum diagram of 0%Mn-OAWH, 20%Mn-OAWH and 50%Mn-OAWH nanoparticles in Example 1; wherein A is the particle size distribution diagram and TEM diagram of 0%Mn-OAWH nanoparticles; B is the particle size distribution diagram and TEM diagram of 20%Mn-OAWH nanoparticles; C is the particle size distribution diagram and TEM diagram of 50%Mn-OAWH nanoparticles; D is the XRD diagram of each nanoparticle; E is the EDS energy spectrum diagram of 20%Mn-OAWH nanoparticles; F is the EDS energy spectrum diagram of 50%Mn-OAWH nanoparticles.

[0015] Figure 2 FTIR characterization, dispersion experimental results and EDS Mapping diagram in Example 2; A is the FTIR spectrum of 0% Mn-OAWH, 20% Mn-OAWH, 50% Mn-OAWH and APWH nanoparticles; B is the dispersion difference of each nanoparticle in dichloromethane; C is the dispersion difference of each nanoparticle in polycaprolactone dissolved in dichloromethane; D is the EDS Mapping diagram of 20% Mn-OAWH / PCL composite scaffold.

[0016] Figure 3 The effects of the composite scaffold in Example 3 on the proliferation of rat bone marrow mesenchymal stem cells under normal conditions and under oxidative stress conditions, as well as its ability to scavenge reactive nitrogen and reactive oxygen species, are explored; wherein A is the proliferation of rBMSCs cells after being cultured with the culture medium of each group of composite scaffold extracts under normal conditions; B is the proliferation of rBMSCs cells after being cultured with the culture medium of each group of composite scaffold extracts under oxidative stress conditions; C is the scavenging rate of PCL, 0% Mn-OAWH / PCL and 20% Mn-OAWH / PCL for DPPH and superoxide anions.

[0017] Figure 4 ALP staining of rBMSC cells treated with osteogenic induction medium containing the composite scaffold extract in Example 4 for 14 days.

[0018] Figure 5 The establishment of the critical bone defect model in rats, the implantation of the scaffold, and the bone regeneration after 8 weeks in Example 5; A is the establishment of the critical bone defect model in rats and the implantation of the scaffold; B is the Micro-CT three-dimensional reconstruction image after 8 weeks. DETAILED DESCRIPTION

[0019] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0020] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.

[0021] Example 1: 4 mL of oleic acid and 16 mL of anhydrous ethanol were added to a 50 mL beaker and stirred at 600 rpm for 10 min at room temperature to form a uniform solution. Subsequently, 4.5 mL of 0.25 M CaCl2 aqueous solution, 0.40 mL of 0.25 M MgCl2 aqueous solution, 0.10 mL of 0.25 M MnCl2 aqueous solution and 5 mL of 0.15 M Na3PO4 aqueous solution were added to the mixture in sequence, and the mixture was stirred at 600 rpm for 20 min at room temperature. The resulting mixture was transferred to a 50 mL polytetrafluoroethylene-lined reactor and heated at 200°C for 12 h. After cooling to room temperature, the precipitate was collected by centrifugation and washed three times with ethanol to remove impurities. Finally, the product was dried in an oven at 40°C for 24 h and ground into fine powder to obtain Mn-OAWH nanoparticles with a manganese content of 20% (referred to as 20%Mn-OAWH).

[0022] To synthesize Mn-OAWH nanoparticles with different manganese contents, the same procedure as for the preparation of 20% Mn-OAWH was used, but the amounts of MgCl2 and MnCl2 aqueous solutions were adjusted: 0.25 mL MgCl2 and 0.25 mL MnCl2 aqueous solutions were used, respectively, to prepare Mn-OAWH nanoparticles with a manganese content of 50% (50% Mn-OAWH).

[0023] For the synthesis of oleic acid functionalized whitlockite nanoparticles without Mn substitution (0%Mn-OAWH), the amount of MgCl2 aqueous solution was adjusted to 0.5 mL and MnCl2 was omitted.

[0024] like Figure 1 As shown in Figures AC, the nanoparticles are spherical with a diameter of about 17 nm; XRD analysis proves that the synthesized nanoparticles are white calcium phosphate ( Figure 1 D); EDS spectrum characterization showed that Mn existed in the synthesized 20%Mn-OAWH and 50%Mn-OAWH, proving that manganese ions successfully replaced part of magnesium ions ( Figure 1 E and F).

[0025] Example 2: After preparing 0% Mn-OAWH, 20% Mn-OAWH, and 50% Mn-OAWH nanoparticles according to the steps of Example 1, they were added to polycaprolactone dissolved in dichloromethane, with a mass ratio of nanoparticles to polycaprolactone of 3:7. Stirring was continued until the dichloromethane evaporated, and a composite scaffold with uniform pore size and specific shape was prepared using a 3D printer through fused deposition modeling technology, thereby obtaining nanoparticle / polymer composite scaffolds (0% Mn-OAWH / PCL, 20% Mn-OAWH / PCL, 50% Mn-OAWH / PCL composite scaffolds) with good dispersibility and antioxidant activity.

[0026] FTIR characterization results show that compared with the traditional aqueous phase synthesis method (APWH), the surface of the calcium phosphate nanoparticles synthesized with oleic acid and anhydrous ethanol as a mixed solvent is coated with oleic acid ( Figure 2 The results of the dispersion test showed that the dispersion of oleic acid-coated manganese-substituted leucodelite nanoparticles in dichloromethane and polycaprolactone dissolved in dichloromethane was better than that of the traditional aqueous leucodelite ( Figure 2 B and C). EDS spectrum characterization showed that the Ca, Mg, Mn and P elements in the 20% Mn-OAWH / PCL composite scaffold were uniformly distributed, indicating that the oleic acid-coated manganese-substituted whitlockite nanoparticles were uniformly dispersed in polycaprolactone ( Figure 2 Middle D).

[0027] Example 3: 0% Mn-OAWH / PCL, 20% Mn-OAWH / PCL, and 50% Mn-OAWH / PCL composite scaffolds were prepared according to the steps of Example 1 and Example 2. First, cell proliferation was detected, indicating that the molar concentration of manganese ions at 20% or less had no significant effect on the proliferation of rat bone marrow mesenchymal cells (rBMSCs) ( Figure 3 The complete culture medium was replaced with the composite scaffold extract culture medium, and 200 μmol / L H2O2 was added to establish the oxidative stress cell model. CCK-8 experiments were performed 1 and 3 days later. The results showed that the OD values ​​of the Control+H2O2, PCL+H2O2 and 0%Mn-OAWH / PCL+H2O2 groups on the 1st and 3rd days were lower than those of the Control group, indicating that the oxidative stress cell model was successfully established. However, the OD value of the 20%Mn-OAWH / PCL+H2O2 group was comparable to that of the Control group without H2O2, indicating that the 20%Mn-OAWH / PCL composite scaffold released Mn 2+ Effectively remove reactive oxygen species, protect rBMSCs from oxidative stress, and promote subsequent bone defect repair ( Figure 3Middle B). DPPH detection kit and superoxide anion detection kit were used to evaluate the ability of 20%Mn-OAWH / PCL scaffolds to scavenge reactive nitrogen and reactive oxygen species. The results showed that the PCL group and the 0%Mn-OAWH / PCL group had almost no antioxidant capacity. In contrast, the 20%Mn-OAWH / PCL group showed strong antioxidant activity ( Figure 3 Middle C).

[0028] Example 4: 0% Mn-OAWH / PCL and 20% Mn-OAWH / PCL composite scaffolds were prepared according to the steps of Examples 1 and 2. The effect of the composite scaffold extract on rBMSCs was determined by alkaline phosphatase (ALP) staining. After 14 days of cell treatment, the number of ALP-positive cells in the composite scaffold extract group increased significantly compared with the control group, and the staining became darker, and showed a manganese ion concentration dependence ( Figure 4 ).

[0029] Example 5: 0% Mn-OAWH / PCL and 20% Mn-OAWH / PCL composite scaffolds were prepared according to the steps of Examples 1 and 2, and each group of composite scaffolds was implanted into the critical bone defect of rat skull ( Figure 5 Middle A). Compared with the Control group, PCL group and 0%Mn-OAWH / PCL group, the 20%Mn-OAWH / PCL group had the best effect in promoting bone tissue regeneration. ( Figure 5 Middle B).

[0030] The above are only preferred embodiments of the present invention. It should be pointed out that, for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention. These should also be regarded as the protection scope of the present invention. These will not affect the effect of the implementation of the present invention and the practicality of the patent.

Claims

1. An oleic acid-coated manganese-substituted whitlockite nanoparticle, characterized in that: Prepared by the following method: A mixed aqueous solution of calcium chloride, magnesium chloride, manganese chloride and sodium phosphate is added to a container containing oleic acid and anhydrous ethanol, and after being stirred evenly, the reaction mixture is reacted at 150-200° C. for 10-12 h to obtain a mixture of manganese-substituted leucodelite nanoparticles immersed in a mixed solution of oleic acid and ethanol, and after centrifugal washing, oleic acid-coated manganese-substituted leucodelite nanoparticles are obtained; The molar ratio of calcium chloride, magnesium chloride, manganese chloride and sodium phosphate is 9:0-1:0-1:6; and the volume ratio of oleic acid and anhydrous ethanol is 4-5:

16.

2. The oleic acid-coated manganese-substituted whitlockite nanoparticles according to claim 1, characterized in that: The molar ratio of the total molar amount of calcium chloride, magnesium chloride and manganese chloride to sodium phosphate is 9:1:

6.

3. An application of the oleic acid-coated manganese-substituted whitlockite nanoparticles according to claim 1 or 2, characterized in that: It is used to prepare nanoparticle / polymer composite scaffolds with good dispersibility and antioxidant activity.

4. Use of the oleic acid-coated manganese-substituted whitlockite nanoparticles according to claim 1 or 2, characterized in that: It is used in the preparation of drugs for anti-oxidation and bone defect repair.

5. A nanoparticle / polymer composite scaffold with good dispersibility and antioxidant activity, characterized in that: Prepared by the following method: Take the oleic acid-coated manganese-substituted white calcium phosphate nanoparticles according to claim 1 or 2, add them to polycaprolactone dissolved in dichloromethane, continue stirring until the dichloromethane evaporates, and use a 3D printer through the fused deposition modeling technology to prepare a composite scaffold with uniform pore size and specific shape to obtain a nanoparticle / polymer composite scaffold with good dispersibility and antioxidant activity.

6. The nanoparticle / polymer composite scaffold with good dispersibility and antioxidant activity according to claim 5, characterized in that: The mass ratio of the oleic acid-coated manganese-substituted whitlockite nanoparticles to polycaprolactone is 1:1-10.

7. The nanoparticle / polymer composite scaffold with good dispersibility and antioxidant activity according to claim 5, characterized in that: The mass fraction of the oleic acid-coated manganese-substituted whitlockite nanoparticles is 30%.

8. An application of the nanoparticle / polymer composite scaffold with good dispersibility and antioxidant activity according to any one of claims 5 to 7, characterized in that: It is used to prepare a composite scaffold that promotes the repair of bone defects under oxidative stress.

Citation Information

Patent Citations

  • Composite nano fiber support material, as well as preparation method and application in bone repairing aspect

    CN102499997A

  • Whitlockite and method for manufacturing the same

    CN103569985A

  • Minimally invasive orthopedic implant composition

    CN105013017A

  • Preparation method and product of composite bioactive ceramic support for bone regeneration and repair

    CN110694103A

  • Preparation method of green fluorescent xonotlite nanocrystal

    CN112251225A